Kecemasan Akademik Mahasiswa Menjelang Ujian Ditinjau dari Jenis Kelamin (SUKMA : Jurnal Penelitian Psikologi, 2020)
Academic anxiety is one of the psychological problems that is often experienced by students. Academic anxiety is related to the existence of anxious feelings about the dangers that will come from the academic institution environment including teachers and certain subjects or subjects. This study aims to find out how the differences in students' academic anxiety towards the Final Semester Examination in terms of gender The research subjects numbered 120 people taken using cluster sampling techniques so that all faculties can be represented. The measuring instrument used was an academic anxiety measurement tool. The analytical method used is the t test. Based on the calculation of differences in academic anxiety between male and female students the sig values of 0.089 ? 0.05 were obtained. This shows that there is no significant difference between academic anxiety in male and female students. The average (mean) academic anxiety in male students is 62.89 with a standard deviation of 1.164 while the average female is 60.00 with a standard deviation of 1.213. Both groups of male and female students experienced academic anxiety towards the End of Semester Evaluation (EAS) so there was no significant difference in academic anxiety.Keyword : Academic Anxiety; student Kecemasan akademik merupakan salah satu problem psikologis yang seringkali dialami oleh mahasiswa. Kecemasan akademik berkaitan dengan adanya perasaan cemas mengenai bahaya yang akan datang dari lingkungan lembaga akademik termasuk pengajar dan mata pelajaran ataupun mata kuliah tertentu. Penelitian ini bertujuan untuk mengetahui bagaimana perbedaan kecemasan akademik mahasiswa menjelang Ujian Akhir Semester ditinjau dari jenis kelamin Subjek penelitian berjumlah 120 orang yang diambil menggunakan teknik cluster sampling agar semua fakultas dapat terwakili. Alat ukur yang digunakan adalah alat ukur kecemasan akademik. Metode analisi yang digunakan adalah uji t. Berdasarkan perhitungan perbedaan kecemasan akademik antara mahasiswa laki-laki dan perempuan diperoleh hasil nilai sig 0,089 ? 0,05. Hal ini menunjukkan tidak terdapat perbedaan yang signifikan antara kecemasan akademik pada mahasiswa laki-laki dan prempuan. Rata-rata (mean) kecemasan akademik pada mahasiswa laki-laki sebesar 62,89 dengan standar deviasi 1,164 sedangkan rata-rata perempuan sebesar 60,00 dengan standar deviasi 1,213. Kedua kelompok mahasiswa laki-laki dan perempuan sama-sama mengalami kecemasan akademik menjelang Evaluasi Akhir Semester (EAS) sehingga tidak terdapat perbedaan yang signifikan pada kecemasan akademik. Kata kunci: Kecemasan akademik, mahasiswa